Pre-service Teachers’ Perspective on the Use of Short Video Stories in Primary Education - Ravenska Tiara Jessica; Ananda, Putri; Wulandari, Nadia; Ratna Prasasti Suminar; Farah Sukmawati Wahidah (Universitas Islam Negeri Palopo, 2025)
This study examines a single pre-service teacher's perspective on using short story videos to teach English to primary school students, utilizing the Technological Pedagogical Content Knowledge (TPACK) model and a constructivist approach. Rather than relying on classroom observations, it emphasizes the teacher’s self-reported experiences and reflections to explore the integration of content knowledge, pedagogical strategies, and technological tools. Data were gathered through a semi-structured interview conducted during the participant’s teaching practicum in a fifth-grade classroom. The participant, a 24 years old undergraduate student in her final year, actively engaged in classroom instruction during her practicum and had completed relevant coursework in English language teaching. Findings indicate that short story videos were viewed as engaging and pedagogically valuable, although the integration across TPACK domains was inconsistent. While the participant maintained a positive attitude towards using video media, she encountered challenges related to technological confidence and the alignment of media with content. This study underscores that TPACK-based reflective interviews can yield valuable insights into the development of preservice teachers, even in the absence of direct classroom observation.